1996
DOI: 10.1021/la951041p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Surface Properties of Novel Fluoroalkylated Flip-Flop-Type Silane Coupling Agents

Abstract: New fluoroalkylated oligomeric silane coupling agents containing morpholino groups were prepared by the reactions of fluoroalkanoyl peroxides with trimethoxyvinylsilane and acryloylmorpholine. The modified glass surface treated with these silane coupling agents was shown to have a strong hydrophilicity with good oil repellency, and these fluoroalkylated oligomers are applicable to new flip-flop-type silane coupling agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 14 publications
(5 reference statements)
1
39
1
Order By: Relevance
“…The relatively higher feed amounts (0.44-0.88 mmol) of Glu-Si(OEt) 3 in the nanocomposite preparation illustrated in Scheme 1 would enable the smooth surface arrangement of the hydrophilic gluconamide segments to provide the completely superhydrophilic surface through the flip-flop motion between the fluoroalkyl groups and gluconamide segments in the nanocomposites. A similar flip-flop motion between longer fluoroalkyl groups and hydrophilic segments has been already reported to exhibit the hydrophilic characteristic with an oleophobic property on the modified surfaces [24][25][26][27][28]. Therefore, the nanocomposites which were prepared under relatively lower feed amounts (0.03 mmol) of Glu-Si(OEt) 3 , can supply a highly oleophobic/superhydrophobic characteristic (dodecane and water contact angle values: 112 and 180 degrees) on the modified surface, due to the lower content of hydrophilic gluconamide segments in the nanocomposites.…”
Section: Resultssupporting
confidence: 73%
“…The relatively higher feed amounts (0.44-0.88 mmol) of Glu-Si(OEt) 3 in the nanocomposite preparation illustrated in Scheme 1 would enable the smooth surface arrangement of the hydrophilic gluconamide segments to provide the completely superhydrophilic surface through the flip-flop motion between the fluoroalkyl groups and gluconamide segments in the nanocomposites. A similar flip-flop motion between longer fluoroalkyl groups and hydrophilic segments has been already reported to exhibit the hydrophilic characteristic with an oleophobic property on the modified surfaces [24][25][26][27][28]. Therefore, the nanocomposites which were prepared under relatively lower feed amounts (0.03 mmol) of Glu-Si(OEt) 3 , can supply a highly oleophobic/superhydrophobic characteristic (dodecane and water contact angle values: 112 and 180 degrees) on the modified surface, due to the lower content of hydrophilic gluconamide segments in the nanocomposites.…”
Section: Resultssupporting
confidence: 73%
“…When oil droplets were placed, the hydrophilic units were pushed flat on the surface allowing fluoroalkyl units (Rf) to assume erectile positions -hence making the surface more oilrepellent. Alterations in the positioning of Rf and hydrophilic units are referred to as the "flip-flop" characteristic of FAAO-incorporated coating materials 13) . The spin coating technique employs a centrifugal force to spread the coating material homogenously over the entire substrate to form a thin and smooth surface.…”
Section: Discussionmentioning
confidence: 99%
“…Further on wettability, it has been reported that the superhydrophobicity and superhydrophilicity of surfaces are key properties for the fabrication of self-cleaning surfaces 10) . In 1990s, Sawada et al introduced a newly categorized chemical compound with a self-cleaning property, constituting the first generation of current "fluoroalkylated acrylic acid oligomer" (FAAO) [11][12][13] . A FAAO is generally synthesized by the polymerization of acrylic acid with difluoroalkanoyl peroxides (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the higher surface tension of water, which results in the respective Young's contact angles 20 satisfying θ water > θ oil . A few studies 14,[21][22][23][24][25][26] have reported surfaces where θ water < θ oil , which was achieved by using specific interactions between water and the substrate to lower the solid-liquid interfacial tension (γ sl ). However, with two exceptions 14,25 all such surfaces were oleophilic.…”
mentioning
confidence: 99%